Emotional Intelligence as a Moderator in the Relationship between Occupational Stress and Organizational Citizenship Behavior among Nigerian Graduate Employees - Aderibigbe, John K.; Mjoli, Themba Q. (Journal of Economics and Behavioral Studies, 2019)
The study investigated emotional intelligence as a moderator in the relationship between occupational stress and organizational citizenship behavior among graduate employees in Nigeria. The purpose of the study was in twofold: firstly, to empirically examine the relationship between occupational stress and organizational citizenship behavior. Secondly, to empirically investigate if emotional intelligence would moderate the relationship between occupational stress and organizational citizenship behavior. The study was conducted to demonstrate whether the presence of emotional intelligence could result in a better level of employee performance, even as employees experience a certain level of occupational stress. In view of the above, the study has contributed to the formation of a new model of psychological intervention for occupational stress and organizational citizenship behavior. The study adopted the positivist explanatory cross-sectional (survey) research design to systematically sample opinions of 1,532 male and female graduate employees across. The various sectors of the Nigerian economy, using a structured and validated questionnaire and version 20 of the Statistical Package for the Social Sciences (SPSS), two hypotheses were stated and analyzed using Pearson Correlation Analysis and Multiple Regression Analysis while the percentage, mean, standard deviation and the frequency of the biographical and occupational data were also determined by the descriptive statistics. The results showed that there was a weak positive relationship between occupational stress and organizational citizenship behavior. Emotional intelligence significantly moderated the relationship between occupational stress and organizational citizenship behavior. Human resource managers should develop emotional intelligence in employees in order to increase the level of organizational performance, and reduce the negative impact of occupational stress. This could be achieved through training and seminar participation. Recommendations of the study could assist in training and developing effective manpower capacity towards improving the economy of the nation.